Performance of Anaerobic Hybrid Membrane Bioreactors Incorporated With Different Sizes of Powdered Activated Carbon and Biogas Production in Treating Palm Oil Mill Effluent - Chai, Huey Yee (2016)
Anaerobic membrane bioreactors (AnMBRs) have been widely used to treat wastewater and powdered activated carbon (PAC) is found as a good material with its adsorption ability. In this project, performance of four external 1 L hybrid AnMBRs which incorporated with different sizes of PAC (sizes in 471.005 0.868 µm 226.824 1.14 µm and 163.884 1.31 µm) were analysed in terms of chemical oxygen demand (COD) removal efficiency, natural organic matter (NOM) removal rate, mixed liquor suspended solid (MLSS), mixed liquor volatile suspended solid (MLVSS), bioflocs formation, flux rate, membrane fouling control and biogas production. It was found that larger surface area by decreasing particle size of PAC could help to enhance microbial growth rate and relatively increase overall anaerobic digestion (AD) rate resulted higher removal efficiencies of organic matter and higher volume of biogas production. In addition, smaller particle sizes of PAC incorporated into polyethersulfone (PES) membrane has resulted highest performance of membrane fouling control by reducing transmembrane pressure (TMP) and produce better quality of effluent compared to membrane without addition of PAC. The best performance of the AnMBRs in COD, protein and polysaccharide removal efficiencies was 90.55 0.21 %, 89.24 1.59 % and 84.96 0.16 % respectively.